2020
DOI: 10.3389/fped.2020.00331
|View full text |Cite
|
Sign up to set email alerts
|

Pet-Keeping in Relation to Asthma, Rhinitis, and Eczema Symptoms Among Adolescents in Kuwait: A Cross-Sectional Study

Abstract: Background: Findings on the associations between household pet-keeping and allergic diseases, including asthma, rhinitis, and eczema, have been contradictory, with investigations reporting positive, negative, and null associations. This study sought to estimate the prevalence of pet-keeping among families in Kuwait and to assess the associations between pet-keeping and symptoms of allergic diseases among adolescents. Methods: Schoolchildren aged 11-14 years (n = 3,864) were enrolled in this cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 50 publications
5
16
1
Order By: Relevance
“…Prior studies have shown that elevated birthweight is associated with eczema development in infancy 51,52 . Among males, our analysis identified that cat‐keeping at birth was associated with increased risk for late‐onset eczema trajectory; this observation has been reported previously 53–55 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Prior studies have shown that elevated birthweight is associated with eczema development in infancy 51,52 . Among males, our analysis identified that cat‐keeping at birth was associated with increased risk for late‐onset eczema trajectory; this observation has been reported previously 53–55 …”
Section: Discussionsupporting
confidence: 78%
“…51,52 Among males, our analysis identified that cat-keeping at birth was associated with increased risk for late-onset eczema trajectory; this observation has been reported previously. [53][54][55] Comparing different studies on eczema trajectories (see The prospective long-term follow-ups that covered childhood, adolescence and early adulthood and the high retention are major strengths to our study. In addition, analysing males and females separately provided novel insights into sex-specific inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in terms of education level and income, our study sample did not substantially deviate from other randomly selected samples in Kuwait. For instance a prior study that enrolled a random sample of parents (n=3864) of high school students in Kuwait reported that 42.7% of mothers and 35.8% of fathers have Bachelor's degree 46 , which is lower than the reported estimate in the current report (57.6% reported having a Bachelor's degree). Moreover, the majority of study participants of the aforementioned study sample reported a household income between 1501 and 3000 Kuwaiti Dinars (44.5%) 47 , which is close to what was reported by participants in the current report (45.5% reported a similar income).…”
Section: Strengths and Limitationscontrasting
confidence: 80%
“…Their practical impact should thus be analysed with great caution on a caseby-case basis. Some authors have also suggested that the protective effect of exposure to pets may only be apparent and may in fact result from selective avoidance of exposure by patients or high-risk individuals [18][19][20]. Neither can the effect of reverse causation be ruled out in the authors' own research, given that the information obtained by means of the questionnaire is limited.…”
Section: Discussionmentioning
confidence: 97%